Impacts of Four Decades of Forest Loss on Vertebrate Functional Habitat on Borneo - Ocampo-Peñuela, Natalia; Garcia-Ulloa, John; Kornecki, Itto; Philipson, Christopher D.; Ghazoul, Jaboury (Frontiers in Forests and Global Change, 2020)
Tropical forests are undergoing drastic transformations, putting at risk the species that rely on them. On the island of Borneo, between 1973 and 2015, 50% of the forest was lost, much of this to oil palm and other industries. We explore the impacts of these four decades of forest loss on the functionally connected habitat of 245 forest birds and mammals. First, we map potential suitable habitat in 1973 and 2015 by refining reported ranges by elevation, forest cover and patch size. We find that, on average, these species have lost 28% of habitat within their ranges. We then use graph-theory connectivity models to calculate the functionally connected area for each species, according to their natal dispersal abilities. We find a mean loss of 35% in functionally connected area, revealing the often hidden impacts of deforestation. Losses in functionally connected habitat are largely driven by area of habitat loss, though maximum elevational range limit also explains some of the differences modeled across species, with lowland species being most affected. We present a vulnerability index of threat arising from loss of functionally connected habitat. The spatial distribution of vulnerability index values serves as a tool for setting conservation priorities for forest remnants on Borneo, given that most of the ranges of these species are not protected. We make recommendations for the use of connectivity models to prioritize resources for research and conservation on Borneo and other biodiversity hotspots.